Particulate dominance of organic carbon mobilization from thaw slumps on the Peel Plateau, NT: Quantification and implications for stream systems and permafrost carbon release - S Shakil; S E Tank; S V Kokelj; J E Vonk; S Zolkos (Environmental Research Letters, 2020)
Climate change is increasing the frequency and intensity of thermokarst, and accelerating the delivery of terrestrial organic material from previously sequestered sources to aquatic systems, where it is subject to further biochemical alteration. Rapid climate change in the glacially conditioned ice-rich and ice-marginal terrain of the Peel Plateau, western Canada, is accelerating thaw-driven mass wasting in the form of retrogressive thaw slumps, which are rapidly increasing in area, volume and thickness of permafrost thawed. Despite major perturbation of downstream sedimentary and geochemical fluxes, few studies have examined changes in flux and composition of particulate organic carbon (POC) in streams and rivers as a result of permafrost thaw. Here we show that the orders of magnitude increase in total organic carbon, nitrogen, and phosphorus mobilized to streams from thaw slumps on the Peel Plateau is almost entirely due to POC and associated particulate nitrogen and phosphorus release. Slump-mobilized POC is compositionally distinct from its dissolved counterpart and appears to contain relatively greater amounts of degraded organic matter, as inferred from base-extracted fluorescence of particulate organic matter. Thus, slump-mobilized POC is potentially more recalcitrant than POC present in non-slump affected stream networks. Furthermore a substantial portion of POC mobilized from thaw slumps will be constrained within primary sediment stores in valley bottoms, where net accumulation is currently exceeding net erosion, resulting in century to millennial scale sequestration of thermokarst-mobilized POC. This study highlights the pressing need for better knowledge of sedimentary cascades, mobilization, and storage reservoirs in slump-affected streams, and baseline assessments of the biodegradability of POC and cycling of particulate nutrients within a sedimentary cascade framework. Explicit incorporation of POC dynamics into our understanding of land-water carbon mobilization in the face of permafrost thaw is critical for understanding implications of thermokarst for regional carbon cycling and fluvial ecosystems.